Hrvaška proza ob koncu prejšnjega tisočletja - Strsoglavec, Đurđa (Slavistična revija, 2002)
The article outlines the prevalent prose models and poetics in Croatian literature at the turn of the last millennium. Some attention is also paid to the characteristics of the previous centuries.
Keywords: 1970/2000; hrvaška književnost; hrvaška proza; poetika; prozni modeli